Malang City MSME Women Entrepreneurs Framed by Sustainability, Digital Economy and Environmental Sustainability - Dwi Ekasari Harmadji; Sukma Perdana (Prodi Akuntansi, Fakultas Ekonomi dan Bisnis, Universitas PGRI Madiun, 2024)
This research aims to understand the role of Malang City MSME Women Entrepreneurs framed in sustainability with the digital economy and environmental sustainability. This research is descriptive qualitative research with data obtained through in-depth interviews and Forum Group Discussions (FGD). Main informant Mrs. Peni Budi Astuti as founder of the Super Preman Organization (abbreviation for: Independent Women Source of Change) in Malang City. The research results provide meaning about the role of social organizations such as Preman Super, whose members are dominated by female entrepreneurs, in the sustainability of MSMEs in the city of Malang. Women entrepreneurs are also accustomed to utilizing the digital economy for the sustainability of their MSMEs. Environmental sustainability through environmentally friendly production processes is also implemented for the sustainability of MSMEs in Malang City. The results of this research can be used for an efficient and effective mentoring program to empower women MSME entrepreneurs initiated by the Malang City Government.